Optimization of biodiesel production from waste cooking oil using ion-exchange resins. Issue 1 (2nd January 2016) - Kolyaei, Maryam; Zahedi, Gholamreza; Nasef, Mohamed Mahmoud; Azarpour, Abbas
ABSTRACT: Waste cooking oil is a potential substitution of refined vegetable oil for the production of biodiesel due to the low cost of raw material and for solving their disposal problem. In this study, optimization of esterification process of free fatty acids in artificially acidified soybean oil with oleic acid has been carried out using methanol as an agent and ion exchange resin as a heterogeneous catalyst. The esterification reaction has been investigated based on the mass balance of the developed model. The model has been validated against experimental data and effects of temperature and catalyst weight have been analyzed. Thereafter, optimization process has been fulfilled for two different objective functions as conversion of acid oil and benefit. Optimization results indicated that the maximum conversion of acid is 95.95%, which is achievable at 4.48-g catalyst loading and reaction temperature of 120°C. Maximum benefit was obtained as US$0.057 per batch of reaction at a catalyst amount of 1 g and temperature of 120°C.